(untitled) (Cadernos de Sociomuseologia, 2014)
This article explores how the itinerancy was used and perceived in Museology over times, in order to enhance its appearance as a practical extension of the museums, and the context in which their use has become more necessary. Assuming the use of itinerancy followed broader museological processes, this article aims demonstrate the use of itinerancy as a phenomenon that falls within an opening movement of popularizing museums and their collections and dialogues, from the mid-twentieth century. Keywords: Museology, itinerancy, cultural accessibility